Microwave-assisted synthesis and characterization of microstar shaped zinc oxide - Gómez, Idalia; Yucam´án, Miguel José; Palomar, Flor (Universidad Autónoma de Nuevo León, 2012)
A microwave-assisted solution-phase approach has been applied for the synthesis ofzinc oxide microstructures. Toe synthesis procedure was carried out by using the reagents: Zinc ni trate and Methenamine, at stoichiometric ratio. Analysis by means ofX-ray Diffraction (XRD) shows a crystalline phase in hexagonal wurtzite arrangement for ZnO. The presence ofmicrostar shaped zinc oxide (2-3μm) with nanorods,f50nm) arranged has been confirmed from High Resolution Scanning Electron Microscopy (HRSEM). The formation of nanorods was confirmed by Transmission Electron Microscopy. In Raman spectroscopy a red shift was detected in the microstructures compared with ZnO bulk. High crystalline materials without additional post-synthesis treatrnent were found.